2021
DOI: 10.1200/jco.20.03614
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Outcome of Neoadjuvant Chemoradiotherapy Plus Surgery for Esophageal Cancer: The Randomized Controlled CROSS Trial

Abstract: PURPOSE Preoperative chemoradiotherapy according to the chemoradiotherapy for esophageal cancer followed by surgery study (CROSS) has become a standard of care for patients with locally advanced resectable esophageal or junctional cancer. We aimed to assess long-term outcome of this regimen. METHODS From 2004 through 2008, we randomly assigned 366 patients to either five weekly cycles of carboplatin and paclitaxel with concurrent radiotherapy (41.4 Gy in 23 fractions, 5 days per week) followed by surgery, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
337
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(353 citation statements)
references
References 27 publications
7
337
3
6
Order By: Relevance
“…Treatment resistance represents a fundamental problem in clinical oncology. In this context, esophageal cancer represents a prime example, because success rates remain low with dismal outcomes and 5-year survival rates ranging from 20% to 38% [1,7,9], indicating that for only a subset of patients, multimodal treatment concepts are effective [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment resistance represents a fundamental problem in clinical oncology. In this context, esophageal cancer represents a prime example, because success rates remain low with dismal outcomes and 5-year survival rates ranging from 20% to 38% [1,7,9], indicating that for only a subset of patients, multimodal treatment concepts are effective [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…A prime example is the CROSS trial, which demonstrated that the median overall survival (OS) was significantly higher in the CRT-plus-surgery group compared to the surgery-only group (48.6 months versus 24.0 months, respectively) [7,8]. Very recently, the follow-up data from the CROSS trial were published, with a 10-year OS of 38% for patients in the CRT-plus-surgery group compared with 25% for patients in the surgery-only group, respectively [9]. Nevertheless, many patients do not benefit from the advances in current treatment strategies, but are exposed to the potential side effects of both CT and irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] The results of the randomized controlled CROSS trial suggested that the OS benefit of patients with locally advanced resectable esophageal or junctional cancer who received preoperative chemoradiotherapy according to CROSS persisted for more than 10 years, which strongly indicated that patients with locally advanced resectable esophageal or junctional cancer could benefit from preoperative neoadjuvant chemoradiotherapy. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the results of the CROSS trial presented a major breakthrough due to improved survival with preoperative chemoradiotherapy among patients with potentially curable esophageal or gastroesophageal junction cancer (included patients: 275 (75%) patients with AC, 84 (23%) patients with SCC, and 7 (2%) patients with large-cell undifferentiated carcinoma) [10]. Recently published data on 10-year-survival outcomes (median followup 147 months) affirm the overall survival benefit for patients receiving neoadjuvant chemoradiotherapy compared to surgery alone (HR 0.70; 95% CI 0.55-0.89; overall OS benefit 13% (38% versus 25%, respectively)) [11].…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%